x(x-11)=3

Simple and best practice solution for x(x-11)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-11)=3 equation:



x(x-11)=3
We move all terms to the left:
x(x-11)-(3)=0
We multiply parentheses
x^2-11x-3=0
a = 1; b = -11; c = -3;
Δ = b2-4ac
Δ = -112-4·1·(-3)
Δ = 133
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-\sqrt{133}}{2*1}=\frac{11-\sqrt{133}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+\sqrt{133}}{2*1}=\frac{11+\sqrt{133}}{2} $

See similar equations:

| P(x)=x^2+10 | | 7y+5=23 | | -1y=6 | | 7+3(2g+6)=-29 | | -4=3m-16 | | 4=(y+10)/2 | | 2t+8=–4(t+1) | | -3-7(1+6d)=28 | | -1/5(w-1)=15 | | -19w=2w+9-6w | | 4x=19-(-17) | | -15+16=86-29p | | 0.25^x-1=8^×+3 | | -2(4x-8)+2x=-5x+10 | | 9f+3f=-34 | | (18+x)1=(15+45)15 | | 4(6n-4)=8-(2n-2) | | −18(z−16)=−38(z+16) | | 18(18+z)=15(45+15) | | (6/5)/7+y=7/2 | | 2a=5+a+3 | | m/30-15=m/30+15+1 | | 7y+28=49 | | 10-4a=18 | | (8t-3)^2=0 | | 13=-4x-11 | | 3p-50=p | | 2a2,a=-1 | | 2x^2−28x-102=0 | | -7v+2(v+6)=-33 | | -5(v-9)=4v-9 | | 65x-2=80-3x |

Equations solver categories